Studi Potensi Wisata dan Kualitas Air di Obyek Wisata Casanova Desa Namu Suro Kabupaten Deli Serdang (Study of Potential for Tourism and Water Quality In Tourism Site Casanova Suro Namu Village Deli Serdang District) - Fajar Prasetya Kembaren; Budi Utomo; Indra Lesmana (AQUACOASTMARINE, 2016)
The river is the mass of water that naturally flows through a valley in theearth's surface from a high place to a lower place. Casanova River is located inDeli Serdang, North Sumatra. Data on objects and attractions as well as thequality of water is needed to determine how large the potential in The RiverCasanova. The purpose of this study to determine the potential of The riverCasanova and tourism activity influence on water quality. This study wasconducted from April to June 2016. Data collections that performed in this studyare water quality data and perception of a community also visitors byquestionnaires. The results showed that the water quality of The River Casanovabased on seven parameters were still correspond to the standard of quality but fortotal coliform, the parameter has exceeded the quality standards under PP No 82of 2001 and the perceptions of visitors already felt comfortable with theseattractions. Assessment of potential objects and the appeal of existing rivertourism in The River Casanova worth 77.40% under appropriate conditionsdeveloped.Keywords: River Casanova, Water Quality, Potential, Total coliform, Travel